1999
DOI: 10.1046/j.1463-1318.1999.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate reconstruction of the anal sphincter after fistulectomy in the management of complex anal fistulas

Abstract: An analysis was made of the indications and outcome of immediate reconstruction of the anal sphincter after fistulectomy in the management of a selected group of patients who were at risk of post-operative incontinence. A total of 31 patients underwent surgery, with 25 high trans-sphincteric fistulas (80.6%), four low trans-sphincteric fistulas (12.9%), and two suprasphincteric fistulas (6.5%). The median post-operative stay was 7.0 days, with a median follow up of 24.0 months. We describe one case (3.2%) of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 5 publications
3
20
0
2
Order By: Relevance
“…This concept was clearly illustrated in a study by van der Hagen et al [45], where the recurrence rate in patients treated by flap or fistulotomy was 22 and 7 % after 12 months and 63 and 39 % after 72 months, respectively. In this review, the weighted average duration of follow-up was 28.9 months, and the success rate was about 90 %, which was also the case in the studies with at least 2 [20,33,34] or 5 years [38] of follow-up. Moreover, the data that emerged from this systematic review seem to confirm the need for a longterm follow-up after fistula surgery: The medium times to recurrence were 20.0 and 17.3 months in the studies by Arroyo et al and Ratto et al,respectively [20,38].…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…This concept was clearly illustrated in a study by van der Hagen et al [45], where the recurrence rate in patients treated by flap or fistulotomy was 22 and 7 % after 12 months and 63 and 39 % after 72 months, respectively. In this review, the weighted average duration of follow-up was 28.9 months, and the success rate was about 90 %, which was also the case in the studies with at least 2 [20,33,34] or 5 years [38] of follow-up. Moreover, the data that emerged from this systematic review seem to confirm the need for a longterm follow-up after fistula surgery: The medium times to recurrence were 20.0 and 17.3 months in the studies by Arroyo et al and Ratto et al,respectively [20,38].…”
Section: Discussionsupporting
confidence: 57%
“…One hundred and seven records were excluded for various reasons; therefore, 17 full-text articles were assessed for eligibility. Fourteen reports satisfied the inclusion criteria [19,20,[28][29][30][31][32][33][34][35][36][37][38][39], while three studies were excluded because their results were updated in a more recent article [40][41][42] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…fiPs has also demonstrated a low risk of morbidity in other published series (table 5). [18][19][20][21][22] in studies that adopted an overlapping sphincteroplasty, 17,23,24 no dehiscence was reported (table 5). however, it should be taken into account that, when performed to treat fecal incontinence due to anal fistula surgery, overlapping sphincteroplasty can cause bleeding or infective complications in up to 25% of the patients.…”
Section: Discussionmentioning
confidence: 99%